Cross-Cultural Design. User Experience of Products, Services, and Intelligent Environments c - Rau, Pei-Luen Patrick; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This two-volume set LNCS 12192 and 12193 constitutes the refereed proceedings of the 12th International Conference on Cross-Cultural Design, CCD 2020, held as part of HCI International 2020 in Copenhagen, Denmark in July 2020. The conference was held virtually due to the corona pandemic. The total of 1439 papers and 238 posters included in the 40 HCII 2020 proceedings volumes was carefully reviewed and selected from 6326 submissions. The regular papers of Cross-Cultural Design CCD 2020 presented in this volume were organized in topical sections named: Cross-Cultural User Experience Design; Culture-Based Design, Cross-Cultural Behaviour and Attitude, and Cultural Facets of Interactions with Autonomous Agents and Intelligent Environments.
Cross-Cultural User Experience Desig -- Culture-Based Design -- Cross-Cultural Behaviour and Attitude -- Cultural Facets of Interactions with Autonomous Agents and Intelligent Environments.
Keywords: User interfaces (Computer systems).; Human-computer interaction; Coding theory; Information theory; Social sciences -- Data processing; 9; Education -- Data processing; Machine learning; User Interfaces and Human Computer Interaction; Coding and Information Theory; Computer Application in Social and Behavioral Sciences; Computer Communication Networks; Computers and Education; Machine Learning